Inbreeding depression level of post-larvae freshwater prawn (Macrobrachium rosenbergii) from several hatcheries in Java, Indonesia - ROBI BINUR; ADI PANCORO (Society for Indonesian Biodiversity, 2017)
Binur R, Pancoro A. 2017. Inbreeding depression level of post-larvae freshwater prawn (Macrobrachium rosenbergii) from several hatcheries in Java, Indonesia. Biodiversitas 18: 609-618. Inbreeding accumulation will tend to reduce genetic variation or depressed of the prawn fry produced. This problem has caused a decrease in production and quality of prawns culture in Indonesia. The purpose of this study is to measure the level of inbreeding depression prawn fry generated from several hatcheries in Java by microsatellite markers. There is four microsatellite locus to be used i.e Prk9A/T1, Prk4G/T1, TGFP16, and Mr8-88. The amplification of fourth locus using PCR with 6-carboxy-fluorescine (6-FAM) label. The number of alleles (Na) from fourth locus is Mr8-88 (11 alleles), TGFP16 (10 alleles), Prk4G/T1 (9 alleles), dan Prk9A/T1 (5 alleles), respectively. The level of polymorphism locus from highest to lowest is locus Prk4G/T1 (0.703), Prk9A/T1 (0.507), TGFP16 (0.410), and Mr8-88 (0.370), respectively. Inbreeding depression level of postlarvae (PL) M. rosenbergii tend to moderate with BBI Ciamis (He 0.444), BBUG Samas (He 0.514), LRPTBPAT Sukamandi (He 0.519), and UPBL Probolinggo (He 0.530), respectively. AMOVA analysis showed about 8.0% genetic variation among populations. From these results, it can be concluded that the PL produced indicated have been depressed. Post-larvae prawns produced from fourth hatcheries is not recommended to be a broodstock but can be used for cultivation for farmers.